Rotifers of Kepektas Dam Lake (Elazig-Turkey) - Saler, S. (Shiraz University, 2009)
With the aim of identifying the Rotifera fauna of Kepektas Dam Lake, samples were collected monthly between January-December 2005. In total 11 rotifer species were identified. As a species-wise percentage, Kellicttia longispina had the highest level with 57%. When the annual abundance of species was taken into consideration Polyarthra vulgaris, Colurella uncinata, Asplanchna priodonta and Keratella cochlearis were determined as dominant species. These species were observed in most months of the year and were well observed in their annual abundance. Notholca squamula was classified as cold steno-thermal species, as this species was recorded only in February and March. Increases in Rotifer individual numbers were observed in spring and summer months. © Shiraz University.
Keywords: Kepektas Dam Lake; Rotifer abundance; Rotifer distribution; Rotifer seasonal variation; Rotifera; Turkey